2011
DOI: 10.1038/nrc3174
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of cancer development in obesity

Abstract: The increasing incidence of obesity and its co-morbid conditions poses a great challenge to global health. In addition to cardiovascular disease and diabetes, epidemiological data demonstrate a link between obesity and multiple types of cancer. The molecular mechanisms underlying how obesity causes an increased risk of cancer are poorly understood. Obesity disrupts the dynamic role of the adipocyte in energy homeostasis, resulting in inflammation and alteration of adipokine (for example, leptin and adiponectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
658
1
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 767 publications
(678 citation statements)
references
References 164 publications
6
658
1
13
Order By: Relevance
“…Epidemiological studies link obesity with several types of cancers. 6,34 However, the biological mechanisms underlying the link between obesity and cancer and the possible role of p53 in this pathway are still poorly understood. Abrogation of p53 function, by its deficiency or mutation, apparently results in aberrant differentiation, which may give rise to transformed cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies link obesity with several types of cancers. 6,34 However, the biological mechanisms underlying the link between obesity and cancer and the possible role of p53 in this pathway are still poorly understood. Abrogation of p53 function, by its deficiency or mutation, apparently results in aberrant differentiation, which may give rise to transformed cells.…”
Section: Discussionmentioning
confidence: 99%
“…4 Disruption of normal metabolic homeostasis in obesity leads to the development of several pathological conditions such as insulin resistance, type 2 diabetes and increased risk of development of a variety of cancers. 2,5,6 Results from several studies indicated that there is an inverse correlation between BAT activity and obesity. [7][8][9] Thus, increasing brown adipose tissue mass or activity could be a useful approach to limit obesity and its associated disease states.…”
mentioning
confidence: 99%
“…Excess adipose tissue leads to metabolic changes such as reduced high-density lipoprotein cholesterol, elevated triglycerides, hypertension, and insulin resistance (Khandekar et al, 2011). Obesityinduced esophageal reflux, hypertension, insulin resistance, and hormone alternations could contribute to an increased risk in esophageal, kidney, colorectal, and breast cancers, respectively (Wang and Dubois, 2012).…”
Section: Allium Cepa Leffects On Proliferation Of Cancer Cells and Amentioning
confidence: 99%
“…It has been reported that increase in visceral adipose tissue above the normal level (represented by waist circumference >102 cm in men and > 88 cm in women) is a risk factor in esophageal cancer and, to a lesser extent, colorectal cancer [54]. A strong association was reported between adipose tissue in the abdominal area (visceral fat) and increased levels of inflammatory markers leading to cancer initiation as a result of the imbalance in the counter-regulating hormones such as leptin and adiponectin [55]. Leptin and adiponectin were found to be inversely associated with body weight changes: those with higher body weights have higher levels of leptin, while those with lower body weight have higher adiponectin levels [56].…”
Section: Role Of Adipose Tissues In Cancer Developmentmentioning
confidence: 99%